Single ultrasound-guided local high-dose thrombin injection in the treatment of giant brachial artery pseudoaneurysm: A case report. Issue 33 (19th August 2022) - Li, Liang; Xiu, Junqing; Yuan, Lian; Zhang, Xing; Li, Yue
Abstract : Rationale: Pseudoaneurysm (PSA) is a common complication related to vascular intervention, and surgical therapy is the primary method. However, a giant brachial artery PSA over 2 weeks is rarely observed. Due to the adhesion of surrounding tissue, thrombus organization, the extensive injury, and the high expense of transluminal stent-graft placement, a single ultrasound-guided local high-dose thrombin injection can be a therapy option. Such cases are rarely reported. Patient concerns: A 71-year-old man with a history of left elbow fossa interventional puncture presented to our hospital with a pulsatile mass in the left elbow fossa. He had a history of cerebral infarction 32 years prior without sequelae, emphysema for more than 2 years, hyperlipidemia for 3 months, and prostatic hyperplasia for 8 months. After conservative therapy, the lumbar compression fracture produced by trauma 24 years ago healed, and the intracranial hematoma induced by trauma ten years ago was absorbed. Diagnosis: Ultrasound examination showed giant mixed echoes on the posterior medial side of the left brachial artery. Interventions: The patient underwent a single ultrasound-guided local high-dose thrombin injection to treat giant brachial artery PSA. Outcomes: Following therapy, the ultrasonography revealed that extensive thrombosis immediately formed in the cavity, and the internal blood flow signals had completely vanished. A week later, a physical examination showed that the PSA had shrunk with no apparent tenderness and that the texture had hardened. Pulsation and vascular murmurs disappeared. Ultrasound showed that the PSA was reduced, and no blood flow signals were found. Lessons: A single ultrasound-guided local high-dose thrombin injection had a considerable effect in curing large iatrogenic PSA. However, when deciding on the best therapy, specificity must be taken into account.